IMPLEMENTASI MULTIMEDIA DALAM PEMBELAJARAN PENGENALAN HURUF ABJAD UNTUK PENDIDIKAN ANAK USIA DINI (PAUD) - Yulianti, Liza; Jumadi, Juju; Zulita, Leni Natalia (UNIVED Press, 2013)
This study aims to determine how to design, build and test a multimedia software for media introduction of the alphabet with Macromedia Flash 8.0. The purpose of this study is the media making to introduce the letters of the alphabet in Early Childhood. Working procedure of making the application of introduction letter of the alphabet is determining the material, making the display format, the display and determine the final design is a trial. After doing research through these stages, the obtained results of the study in the form of application. Highlights in this application is the introduction of the letter, guess letters, and charades developed with Macromedia Flash 8.0. Making these applications are expected to be useful for education, especially in early childhood, and can be used as a reference in the form of interactive multimedia learning media.